Improved bilateral teleoperation with proactive haptic sensing and transmission. (January 2018) - Kuzu, Ahmet; Baran, Eray A.; Bogosyan, Seta; Gokasan, Metin; Sabanovic, Asif
This article presents a novel master-slave control configuration that is experimentally demonstrated to improve teleoperation performance under random network delay. This is achieved via the design of a proactive haptic sensing system based on a laser range sensor on the slave side, which in turn allows for the proactive transmission of force control from the master to the slave, thus compensating for Internet-based network delays. The proposed configuration introduces three main contributions to the literature of bilateral control systems: (1) fully decoupled position and force control systems, which allow for the controller gains of each loop to be tuned independently, eliminating the trade-off common to most previous literature; (2) a novel approach that exploits the slow variation nature of the environment parameters, resulting in a lower bandwidth requirement in comparison to previous force control methods; (3) capability to measure the slave environment location and the prediction of the contact force as a result, which provides the human operator with the capability to generate the reaction force proactively on the master side. The conducted experiments demonstrated a significantly improved performance in terms of synchronized forces and positions despite the random network delay between the master and slave systems.